Overestimating Reported Prejudice Causes Democrats to Believe Disadvantaged Groups Are Less Electable. Issue 1 (17th March 2022) - Mercier, Brett; Celniker, Jared B.; Shariff, Azim F.
Abstract : Four studies show that Democrats overestimate the explicit prejudice reported by the American electorate, leading them to perceive presidential candidates from disadvantaged groups as less electable. Study 1 (MTurk; n = 728) found that Democrats overestimated the percentage of Americans who say they would not vote for presidential candidates from disadvantaged groups. Study 2 (MTurk; n = 597) replicated this finding and demonstrated that Democrats who perceive high levels of explicit prejudice toward a group also believe presidential candidates from that group are less electable. Moreover, Democrats who more frequently interacted with Republicans were more accurate in estimating the amount of explicit prejudice reported by Republicans, Democrats, and Americans in general. Studies 3A (Prolific; n = 930) and 3B (YouGov; n = 747) found that presenting information about true levels of reported prejudice made Democrats believe generic presidential candidates from disadvantaged groups would be more electable. We did not find evidence that information about true levels of reported prejudice affected Democrats' beliefs about the electability of specific candidates in the 2020 Democratic Primary or their support for these candidates.